Analysis on the difference of the characteristic between high power IGBT modules and press pack IGBTs. (November 2017) - Deng, Erping; Zhao, Zhibin; Xin, Qingming; Zhang, Jingwei; Huang, Yongzhang
Abstract: The insulated gate bipolar transistor (IGBT) has been widely employed in such applications as alternate current motors and inverters for its lower driving power and lower on-state voltage. IGBT modules and press pack IGBTs are the most commonly used packaging for high-voltage and high-power-density applications. The difference in the packaging style and working conditions between IGBT modules and press pack IGBTs creates distinctions in, for instance, the thermal characteristics and reliability. Those distinctions lead to different applications and working conditions. In this paper, the development of IGBT devices has been reviewed, including the distinction of IGBT modules and press pack IGBTs in packaging style. Most importantly, the thermal and reliability characteristics have been compared in detail and the applications that are most suitable for IGBT modules and press pack IGBTs were outlined. The comparison of the thermal characteristics, reliability and applications provides guidance for users to take full advantage of the devices according to their requirements. Highlights: Two main packaging styles for high power IGBT devices are proposed to compare. The packaging style thermal and reliability characteristics are compared in detail. The application suitable for which IGBT based on those comparisons is concluded. Those comparisons can provide guidance for users to select the suitable IGBTs.